A case of single incision laparoscopic total colectomy for intestinal neuronal dysplasia type B. (2017) - Masuda, Taro; Nonaka, Takashi; Adachi, Toshiyuki; Hisanaga, Makoto; Nagayoshi, Shigeki; Tokunaga, Takayuki; Taniguchi, Ken; Kurohama, Hirokazu; Ito, Masahiro; Fujioka, Hikaru
Highlights: In patients with refractory constipation, it is necessary to care in mind that some patients require surgery. Single incision laparoscopic surgery (SILS) is regarded as the major advance in minimally invasive surgery. Total colectomy by SILS is very useful for the patients with intestinal neuronal dysplasia-type B. Abstract: Introduction: Intestinal neuronal dysplasia type B (IND-B) is an infrequent disease of the submucosal plexus of intestine manifesting chronic intestinal obstruction or severe chronic constipation. IND is rarely reported in adult patients. Presentation of a case: The present study reports on the case of a 36 year-old woman suffering from longstanding chronic constipation and who was diagnosed with severe constipation in more than 20 years. Although she began to take a large amount of stimulant laxatives, such as "senna" and "bisacodyl", constipation symptoms did not improve, she was admitted to our hospital. It was diagnosed with refractory constipation of the medication treatment-resistance, total colectomy with ileorectal anastomosis by single incision laparoscopic surgery (SILS) was performed. The final pathological diagnosis was IND-B. Discussion: Refractory constipation after medical treatment is often seen in young generation. SILS has benefits of better cosmesis, reduced morbidity, reduced postoperative pain, and reduced length of hospital stay. Conclusion: For the patients with refractory constipation associated with neuropathy such as IND, total colectomy by SILS was very effective.